The Sas3p and Gcn5p histone acetyltransferases are recruited to similar genes - Rosaleny, Lorena E (BioMed Central, 2007)
BACKGROUND: Specific histone modifications can perform several cellular functions, for example, as signals to recruit trans-acting factors and as modulators of chromatin structure. Acetylation of Lys14 of histone H3 is the main target of many histone acetyltransferases in vitro and may play a central role in the stability of the nucleosome. This study is focused on the genome-wide binding of Saccharomyces cerevisiae histone acetyltransferases that are specific for Lys14 of histone H3. RESULTS: We have used a variation of the genome-wide location analysis method, based on a macroarray platform, to identify binding sites of yeast histone acetyltransferase catalytic subunits and to correlate their positions with acetylation of Lys14 of histone H3. Our results revealed that the histone acetyltransferases Sas3p and Gcn5p are recruited to a pool of intensely transcribed genes and that there is considerable overlap between the two cohorts of Sas3p and Gcn5p bound gene pools. We also demonstrate a positive correlation between binding sites of both proteins and the acetylation state of Lys14 of histone H3. Finally, a positive correlation between the decrease of H3 Lys14 acetylation in a GCN5 deleted strain and the Gcn5p genome occupancy is shown. CONCLUSION: Our data support a model in which both Gcn5p and Sas3p act as general activators of an overlapping pool of intensely transcribed genes. Since both proteins preferentially acetylate Lys14 of histone H3, our data support the hypothesis that acetylation of this specific residue facilitates the action of the transcriptional apparatus.